Defects in memory B-cell and plasma cell subsets expressing different immunoglobulin-subclasses in patients with CVID and immunoglobulin subclass deficiencies - Blanco, Elena; Pérez-Andrés, Martín; Arriba-Méndez, Sonia; Serrano, Cristina; Criado, Ignacio; Del Pino-Molina, Lucía; Silva, Susana; Madruga, Ignacio; Bakardjieva, Marina; Martins, Catarina; Serra-Caetano, Ana; Romero, Alfonso; et al. (Journal of allergy and clinical immunology, 2019)
BACKGROUND: Predominantly antibody deficiencies (PADs) are the most prevalent primary immunodeficiencies, but their B-cell defects and underlying genetic alterations remain largely unknown. OBJECTIVE: We investigated patients with PADs for the distribution of 41 blood B-cell and plasma cell (PC) subsets, including subsets defined by expression of distinct immunoglobulin heavy chain subclasses. METHODS: Blood samples from 139 patients with PADs, 61 patients with common variable immunodeficiency (CVID), 68 patients with selective IgA deficiency (IgAdef), 10 patients with IgG subclass deficiency with IgA deficiency, and 223 age-matched control subjects were studied by using flow cytometry with EuroFlow immunoglobulin isotype staining. Patients were classified according to their B-cell and PC immune profile, and the obtained patient clusters were correlated with clinical manifestations of PADs. RESULTS: Decreased counts of blood PCs, memory B cells (MBCs), or both expressing distinct IgA and IgG subclasses were identified in all patients with PADs. In patients with IgAdef, B-cell defects were mainly restricted to surface membrane (sm)IgA+ PCs and MBCs, with 2 clear subgroups showing strongly decreased numbers of smIgA+ PCs with mild versus severe smIgA+ MBC defects and higher frequencies of nonrespiratory tract infections, autoimmunity, and affected family members. Patients with IgG subclass deficiency with IgA deficiency and those with CVID showed defects in both smIgA+ and smIgG+ MBCs and PCs. Reduced numbers of switched PCs were systematically found in patients with CVID (absent in 98%), with 6 different defective MBC (and clinical) profiles: (1) profound decrease in MBC numbers; (2) defective CD27+ MBCs with almost normal IgG3+ MBCs; (3) absence of switched MBCs; and (4) presence of both unswitched and switched MBCs without and; (5) with IgG2+ MBCs; and (6) with IgA1+ MBCs. CONCLUSION: Distinct PAD defective B-cell patterns were identified that are associated with unique clinical profiles.
Keywords: lidé; mladiství; Adult; Middle Aged; imunoglobuliny; Immunoglobulins; Female; dítě; B-Lymphocyte Subsets; počet buněk; syndromy imunologické nedostatečnosti; Adolescent; Humans; Plasma Cells; Cell Count; plazmatické buňky; předškolní dítě; lidé středního věku; Child, Preschool; podskupiny B-lymfocytů; mužské pohlaví; mladý dospělý; ženské pohlaví; Young Adult; Aged, 80 and over; senioři nad 80 let; Male; Aged; Child; Immunologic Deficiency Syndromes; dospělí; senioři